การพัฒนากระบวนการสร้างลวดลายบนกระดาษโดยใช้หน้ากากน้ำเพื่อสร้างอุปกรณ์ประเภทกระดาษ - ศตวรรษ กระเดื่องเดช (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
In the past 50 years, electronic devices have been developed by using silicon as the main material. However, silicon has become more expensive and electronic devices have been the cause of electronic waste issues. In recent years, paper substrate has been introduced as alternative to silicon in device development whereas several patterning methods for paper-based device development such as photolithography, wax printing, plotter, ink-jet printing have been proposed. However, these methods are still limited by some issues such as requirement of expensive equipment, incapability of mass production or choices of materials that can be used for patterning etc. Therefore, this work aims to develop a novel method by utilizing an ink-jet printed water pattern as a protective mask for patterning of non-polar solutions onto paper substrate. Its advantages are low cost, mass productive and capable of using a variety of materials. In the experiment, the factors that affect the patterning process including paper type, printing time, solution concentration were studied. Furthermore, we applied this patterning method to fabricate a paper-based lab-on-a-chip for detecting bovine serum albumin and pH.